IMPROVING THE PROFESSIONAL AND PEDAGOGICAL COMPETENCE OF THE FUTURE SCIENCE TEACHER - Nebykova, T.; Nebykov, М. (SWorld-Ger Conference proceedings, 2023)
The main approaches are defined for the formation of the professional and pedagogical competence of the future science teacher. The theoretical meaning of the defined concepts was analyzed: competence, professional and pedagogical competence; determinatio